2021
DOI: 10.1016/j.ijdrr.2021.102521
|View full text |Cite
|
Sign up to set email alerts
|

Coastal inconsistencies: Living with and anticipating coastal flood risks in southern France

Abstract: This work is a contribution to Labex OT-Med (n° ANR-11-LABX-0061) and received funding from Excellence Initiative of Aix-Marseille University-A*MIDEX, a French "Investissements d'Avenir" programme (RISKMED project). Additional funding was provided for the study in France by the European Union-FEDER programme (DIGUE 2020 project).We would also like to thank Claire Mays for carefully reviweing a first version of this manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Individuals and communities "perceive, evaluate and justify" the social, economic, and environmental elements of sustainability. Questions about what is right, what is wrong, what is equitable, and what is the most appropriate solution to a particular problem are repeatedly raised by different social actors in different contexts and often show plurality in people's stances on possible futures (Bertoldo et al 2021).…”
Section: Imagined Futures and Social Identitiesmentioning
confidence: 99%
“…Individuals and communities "perceive, evaluate and justify" the social, economic, and environmental elements of sustainability. Questions about what is right, what is wrong, what is equitable, and what is the most appropriate solution to a particular problem are repeatedly raised by different social actors in different contexts and often show plurality in people's stances on possible futures (Bertoldo et al 2021).…”
Section: Imagined Futures and Social Identitiesmentioning
confidence: 99%
“…Despite the numerous critics of the so-called "deficit models" of science communication [37,40,41], these approaches are still commonly found in applied studies [40,42]. In the field of biodiversity these studies have for example described a "deficiency" in lay people's knowledge of scientific definitions [43,44] and, as a result, have suggested that the public needs to be "better educated" [45,46].…”
Section: Public Understanding Of Biodiversity and Biodiversity Lossmentioning
confidence: 99%